Medical knowledge related to Rocky Mountain spotted fever in Sonora, Mexico. (29th March 2018) - Alvarez-Hernandez, Gerardo; Ernst, Kacey; Acuña-Melendrez, Natalia Haydee; Vargas-Ortega, Anabel Patricia; Candia-Plata, Maria del Carmen
Abstract: Background: Rocky Mountain spotted fever (RMSF) is a tick-borne disease with a high case-fatality rate unless diagnosed promptly and treated timely with doxycycline. Physician knowledge about presentation and treatment can improve outcomes of RMSF in endemic regions, such as Sonora in northern Mexico, where RMSF has caused 1348 non-fatal cases and 247 deaths from 2003 to 2016. Methods: A cross-sectional study was conducted with 343 physicians working in medical facilities in Sonora, Mexico. A 25-item questionnaire explored physician knowledge of clinical, epidemiological and preventive aspects of RMSF. Results: Only 62% of physicians agreed that doxycycline should be used as the first choice treatment for children under 8 years with suspected RMSF. Additionally, 40% of primary care physicians correctly identified the time to initiate doxycycline, and 32% correctly identified the case-fatality rate of untreated RMSF in all patients. Conclusions: Inadequate medical knowledge may adversely affect how patients infected with Rickettsia rickettsii are diagnosed and treated. Educational programs that improve the risk perception and medical knowledge about RMSF should be targeted at physicians most likely to have initial contact with diseased patients.